2
$\begingroup$

Prove $\sum\limits_{n=1}^\infty ne^{-n^2} \leq \frac{3}{2e}$

Perhaps the mean value theorem for each term may work, but I haven't made any progress. I can't seem to reduce it to a geometric series either.

$\endgroup$
1
  • $\begingroup$ Almost there: it is enough to invoke the derivative of a geometric series. $\endgroup$ Commented Dec 18, 2017 at 21:07

2 Answers 2

4
$\begingroup$

Let $f(x) = x\exp(-x^2)$. Note that $f(x)$ is decreasing for $x \geq 1$. Therefore,

\begin{align*} \sum_{n=1}^{\infty}{f(n)} &= f(1) + \sum_{n=2}^{\infty}{f(n)} \\ &\leq \exp(-1) + \int_{1}^{\infty}f(x)dx \\ &= \exp(-1) + \int_{1}^{\infty}x\exp(-x^2)dx \\ &= \exp(-1) -2^{-1}\exp(-x^2)\bigg|_{1}^{\infty} \\ &= \frac{3}{2e} \end{align*}

$\endgroup$
2
$\begingroup$

It is a pretty loose inequality:

$$ \sum_{n\geq 1}n e^{-n^2} = \frac{1}{e}+\sum_{n\geq 2} n e^{-n^2} \leq \frac{1}{e}+\sum_{n\geq 2} n e^{-2n}\leq \frac{6}{5e}\leq\frac{4}{9} $$ since $\sum_{n\geq 2}n x^n = \frac{x^2(2-x)}{(1-x)^2}$ for any $x\in[0,1)$.

$\endgroup$
3
  • $\begingroup$ I wonder can we do it like that $\sum\limits_{n=1}^\infty ne^{-n^2}=e^{-1}+\sum\limits_{n=2}^\infty ne^{-n^2}\leq e^{-1}+\displaystyle\int_2^\infty xe^{-x^2}dx=e^{-1}+\frac{1}{2}e^{-4}<e^{-1}+\frac{1}{2}e^{-1}=\frac{3}{2e}.$ $\endgroup$
    – daulomb
    Commented Dec 18, 2017 at 21:09
  • $\begingroup$ I don't think it is true that $\sum_{n=2}^{\infty}{n\exp(-n^2)} \leq \int_{2}^{\infty}{x \exp(-x^2)dx}$. Check my solution for a similar idea. $\endgroup$
    – madprob
    Commented Dec 18, 2017 at 21:13
  • $\begingroup$ @madroh: I didn't make sure that's why I asked:) $\endgroup$
    – daulomb
    Commented Dec 18, 2017 at 21:15

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .